The China miracle in a technological and socio-political framework—The role of institutions - Ma, Qing-Ping (Routledge, 2020)
China’s economy has grown at an average annual rate of around 9.5% in the past four decades, which is often hailed as the China Miracle. This paper proposes a new theoretical model to analyse the causes of China’s phenomenal growth in a technological and socio-political framework. In our new framework, the contemporary technology (T) determines what an economy can achieve; the objective (O) of the society has a fundamental impact on its economic growth; the performance (P) in implementing the social objective largely determines the growth rate of the economy; and the stability (S) of the society determines the sustainability of the economic growth. China’s institutions have played key roles in the TOPS framework to initiate and sustain China’s rapid growth in the past four decades. Socio-political changes caused by economic growth might affect the capacity of these institutions to promote economic growth in future.